Amniotic fluid pentraxins: Potential early markers for identifying intra‐amniotic inflammatory complications in preterm pre‐labor rupture of membranes. (28th November 2017) - Musilova, Ivana; Andrys, Ctirad; Krejsek, Jan; Drahosova, Marcela; Zednikova, Barbora; Pliskova, Lenka; Zemlickova, Helena; Jacobsson, Bo; Kacerovsky, Marian
Abstract : In this study, pentraxin 3 (PTX3), C‐reactive protein (CRP), and serum amyloid P component (SAP) concentrations in the amniotic fluid of women with preterm pre‐labor rupture of membranes (PPROM) were evaluated based on evidence of microbial invasion of the amniotic cavity (MIAC), intra‐amniotic inflammation (IAI), and microbial‐associated IAI. A total of 149 women with PPROM were included in this study. Amniotic fluid samples were obtained by transabdominal amniocentesis. Amniotic fluid PTX3, SAP, and CRP concentrations were assessed using enzyme‐linked immunosorbent assay. PTX3 and CRP concentrations were higher in women with MIAC, IAI, and microbial‐associated IAI than in women without these conditions. SAP concentrations were only higher in the presence of IAI and microbial‐associated IAI. Amniotic fluid PTX3 concentrations of 11 ng/mL were found to be the best value for identifying the presence of microbial‐associated IAI and IAI in women with PPROM. To conclude, amniotic fluid pentraxins are involved in intra‐amniotic inflammatory responses in pregnancies complicated by PPROM.